Pemanfaatan Tanah Pekarangan Desa di Desa Adat Gelgel Kabupaten Klungkung - Nyoman Andi Widjaya; I Nyoman Gede Sugiartha; Diah Gayatri Sudibya (Fakultas Hukum Universitas Warmadewa, 2021)
Land can be a very basic human desire. The relationship between humans and land can be in the form of a non-secular occult relationship which more or less contains parts of mystical (mystical) powers as the embodiment of humans and their natural surroundings. Inquiry techniques are controlled by radio with knowledge gathering techniques through direct interviews with people who are competent in the theory of reception victimization, reception in complex theories in the construction of the rule of law to see contemporary phenomena in the order of people's lives, especially in the Gelgel environment of Purba Village, Klungkung Regency. The results showed that the use of the Village Grounds in the Purba Gelgel Village was freely leased by the residents of Gelgel Pakraman Village to different parties. The Sanctions of the Traditional Karma of the Gelgel Purba Village which is not in line with the Rights and Obligations of Land Tenure in the Gelgel Ancient Village are following the awig – awig of the Gelgel Purba Village. It is hoped that residents can be vigilant and follow what the Banjar Adat community has united.